Does a multi-stage ultra-endurance run cause de- or hyper hydration? - Knechtle, B.; Kiouplidis, K.; Knechtle, P.; Kohler, G.; Imoberdorf, R.; Ballmer, P. (Journal of Human Sport & Exercise, 2010)
We investigated the changes in body mass and parameters of both renal function and fluid metabolism in a case study in a female ultra-endurance runner during the longest multi-stage mountain ultra-marathon in Europe, the `Swiss Jura Marathon' in 2008. The female ultra-runner performed the 7 stages with a total distance of 175 km, a total ascent of 5,000 m, and a total descent of 8,000 m within 23:11 h: min, finishing as second female runner. By the end of the race, body mass decreased by 0.3 kg, fat mass by 1.2 kg and skeletal muscle mass by 0.7 kg. Haemoglobin and haematocrit decreased by 4.5% and 7.5 %, respectively, and plasma volume increased by 10 %. Serum osmolality decreased by 3.3%. Parameters of myocellular damage increased substantially (CK + 630 %, LDH + 178 % and GOT + 181 %). Creatinine continuously increased in plasma (+ 23 %) and urine (+ 47 %). Creatinine clearance (- 18.7 %), glomerular filtration rate (- 19.4 %) and serum albumin (- 10.6 %) decreased. Urinary specific gravity decreased after each stage and was increased before each stage. Urinary osmolality decreased after each stage and was increased before each stage. The average daily fluid intake from stage 1 to stage 7 (during performance and rest) was 4.9 l per day. Total body water increased by 1.2 l by the end of the race. The potassium-to-sodium ratio in urine was increased after each stage. We assume that the increase in total body water was due to an increased activity in the renin-angiotensin-aldosterone-system as evidenced by the change in urinary electrolytes after the stages and an increased activity of vasopressin as evidenced by increase of urinary osmolality before the stages.